2005
DOI: 10.1088/0034-4885/68/6/r03
|View full text |Cite
|
Sign up to set email alerts
|

Supercooled dynamics of glass-forming liquids and polymers under hydrostatic pressure

Abstract: An intriguing problem in condensed matter physics is understanding the glass transition, in particular the dynamics in the equilibrium liquid close to vitrification. Recent advances have been made by using hydrostatic pressure as an experimental variable. These results are reviewed, with an emphasis in the insight provided into the mechanisms underlying the relaxation properties of glass-forming liquids and polymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

56
1,000
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 681 publications
(1,060 citation statements)
references
References 445 publications
(602 reference statements)
56
1,000
4
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16][17][18] Thus it has been shown that strongly correlating viscous liquids to a good approximation have all eight frequency-dependent thermoviscoelastic response functions [19][20][21] given in terms of just one 22 (i.e., are single-parameter liquids in the sense of having dynamic Prigogine-Defay ratio 19 close to unity 2,20,22 ). Strongly correlating viscous liquids moreover obey density scaling [23][24][25][26][27] to a good approximation, i.e., their dimensionless relaxation timeτ ≡ τρ 1/3 √ k B T /m (where m is the average particle mass) depends on density ρ = N /V and temperature as τ = F(ρ γ /T ). [28][29][30] Paper I 1 presented computer simulations of 13 different systems, showing that van der Waals type liquids are strongly correlating, whereas hydrogen-bonding liquids like methanol or water are not.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18] Thus it has been shown that strongly correlating viscous liquids to a good approximation have all eight frequency-dependent thermoviscoelastic response functions [19][20][21] given in terms of just one 22 (i.e., are single-parameter liquids in the sense of having dynamic Prigogine-Defay ratio 19 close to unity 2,20,22 ). Strongly correlating viscous liquids moreover obey density scaling [23][24][25][26][27] to a good approximation, i.e., their dimensionless relaxation timeτ ≡ τρ 1/3 √ k B T /m (where m is the average particle mass) depends on density ρ = N /V and temperature as τ = F(ρ γ /T ). [28][29][30] Paper I 1 presented computer simulations of 13 different systems, showing that van der Waals type liquids are strongly correlating, whereas hydrogen-bonding liquids like methanol or water are not.…”
Section: Introductionmentioning
confidence: 99%
“…28 However, this correlation is known to be only approximate, with various exceptions having been reported. 29,30 There is no a priori reason why the location of the dielectric loss peak, τ, should be correlated with its width, . Hence, the observed common relationship between and τ in many glassforming liquids, as shown in Figure 1, is unexpected and striking.…”
Section: Experimental Results For the Relationship Between And τmentioning
confidence: 99%
“…This differs from the scaling behavior of isotropic liquids, for which plots of log τ versus T -1 V -γ are nonlinear. 18 The Arrhenius nature of the scaled data for LC implies that V γ reflects the volume-dependence of the height of the activation barrier. The two material constants, Γ and γ, would be equal if τ | were constant along the transition line T c (P).…”
Section: Introductionmentioning
confidence: 99%